Pengaruh Pembiayaan Murabahah dan Musyarakah terhadap Likuiditas BSI dengan NPF sebagai Variabel Intervening: - Faliha Ardhelia Nasution; Tuti Anggraini (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Not the losses it produces, but the failure to maintain cash flow available, is the issue that can result in bankruptcy. Slower than the decline of conventional commercial banks, which was 77.49%, was the decrease of Islamic commercial banks, at 70.13%. This may occur because the borrower finds it challenging to repay the debt, whether out of malice or for other factors beyond the borrower's control. With NPF serving as an intermediary variable, the goal of this study was to ascertain the impact of Musyarakah and Murabahah funding on BSI liquidity. Quantitative SPSS research is employed in this study. 20.0. While for Bank Syariah Indonesia, liquidity is the independent variable (y) and irregular financing is the intermediate variable (z), the effect of murabahah financing (x1) and musyarakah (x2) is the independent or dependent variable. OJK-BSI statistics for the entirety of Indonesia are used in this study as a sample. The study's findings include: 1) that financing through murabaha does not significantly affect the rise in the NPF ratio from 2020 to 2022; 2) that financing through musyarakah does not significantly affect financing the NPF ratio from 2020 to 2022; 3) that financing through murabaha is positively related to liquidity but does not significantly affect liquidity; 4) that financing through musyarakah has a positive relationship with liquidity but does not significantly affect liquidity; and 5) that non-performing financing does not Key words: Murabahah Financing; Musyarakah Financing; Liquidity; Non Performing Financing